5. Respons Indonesia, Malaysia, dan Singapura terhadap Peningkatan Kasus Pembajakan Kapal di Selat Malaka Tahun 2009-2013 - M. Singgih Pangestu; Reni Windiani; Shary Charlotte Pattipeilohy (Journal of International Relations Diponegoro, 2017)
Strait of Malacca (SOM) is one of the most important strait for global trade shipping, yet there’s an increase activity of sea piracy in 2009 which threatened the safety of shipping through the channel. Indonesia, Malaysia, and Singapore as SOM’s coastal states who are perceived to be responsible to the security of SOM took numerous policies to cope with the issue. In this research, writer tried to give depth explanation about reason behind various policies taken by states to tackle the piracy. Perspective of Constructivism of International Relations and Buzan’s theory of Securitization are used as research framework. The result of this research showed that there was a correlation between policies taken by ones state with issue perceived as existential threat. Singapore who constructed sea piracy as threat for its nation tend to take extreme counter-measurement to combat piracy, while Indonesia and Malaysia didn’t really give attention to the issue of piracy since they construct other issues such as illegal fishing and human smuggling as threat to their sovereignty.